Cholate-conjugated cationic polymers for regulation of actin dynamics. Issue 39 (15th September 2022) - Sahoo, Subhasish; Maiti, Ipshita; Laha, Arkayan; De, Rumi; Maiti, Sankar; De, Priyadarsi
Abstract : A cholic acid-conjugated polycationic actin interacting material with self-aggregation behaviour has been synthesized to effectively enhance actin nucleation, and stabilize actin filaments. Abstract : Cytoskeletal movement is a compulsory necessity for proper cell functioning and is largely controlled by actin filament dynamics. The actin dynamics can be fine-tuned by various natural and artificial materials including cationic proteins, polymers, liposomes, and lipids, although most of the synthetic substrates have toxicity issues. Herein, we show actin nucleation and stabilization with a synthetic family of cholic acid (CA)-conjugated cationic macromolecules. Architectural conjugation of CA is designed by attaching it to the polymer chain end, as well as to the side chain of the polymer. The side-chain cholate content is also varied in the copolymer, which results in self-aggregation in aqueous media above a certain critical aggregation concentration (CAC). Below the CAC, the in vitro actin dynamics modulation behaviour is studied using a pyrene actin fluorescence assay, actin co-sedimentation assay, dynamic light scattering (DLS), and transmission electron microscopy (TEM). These polymers are nontoxic to HeLa cells, and the 2% cholate conjugated cationic copolymer showed maximum enhancement of G-actin nucleation, as well as F-actin stabilization. We further develop a theoretical model to elucidate the underlying dynamics of the actin polymerization process under the influence of cationic copolymers with cholate pendants. Finally, we proposed macromolecular self-aggregation as a unique tool for modulating actin dynamics, as revealed from the experimental findings and theoretical modelling.